The Relationship Between Parenting Styles and Bullying Among Adolescents - Andri Nurmansyah; Fifi Siti Fauziah Yani (Inspirasi Foundation, 2026)
Introduction: The Indonesian Teachers’ Union Federation (FSGI) recorded 23 cases of bullying in educational institutions between January and September 2023. The highest incidence was found at the junior high school (SMP) level, accounting for 50% of cases, followed by elementary school (SD) with 13.5%, senior high school (SMA) with 13.5%, and vocational high school (SMK) with 13.5%. The major contributing factors to bullying among school-aged children include parenting styles, peer influence, and school environment. Method: A quantitative research design with a cross-sectional approach was employed. The study population consisted of 1,021 students, from which a sample of 91 students was selected using simple random sampling. Data collection was conducted through questionnaires: parenting styles were measured using the Parenting Style and Dimensions Questionnaire (PSDQ), while bullying incidents were assessed using the Adolescent Peer Relations Instrument. Univariate analysis was performed using frequency distribution, and bivariate analysis was conducted using the Chi-Square test. Result: The findings revealed a significant relationship between parenting styles and bullying incidents (p = 0.000). Bullying among adolescents in schools was influenced by parental upbringing. Parenting styles play a crucial role in shaping children’s personality and behaviour. Adolescents raised under authoritarian parenting styles were found to be at greater risk of becoming perpetrators of bullying, as they tend to replicate daily family interactions in their social environment. Conclusion: This study concludes that parenting styles significantly influence the occurrence of bullying among adolescents. Authoritarian parenting increases the likelihood of adolescents engaging in bullying behavior. Future research is recommended to further investigate the impact of authoritarian and permissive parenting styles on bullying incidents.